2011
DOI: 10.1039/c1nr10797f
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functionalization of fluorescent nanoparticles for specific biolabeling and drug delivery of dopamine

Abstract: The development of fluorescent biolabels for specific targeting and controlled drug release is of paramount importance in biological applications due to their potential in the generation of novel tools for simultaneous diagnosis and treatment of diseases. Dopamine is a neurotransmitter involved in several neurological diseases, such as Parkinson's disease and attention deficit hyperactivity disorder (ADHD), and the controlled delivery of its agonists already proved to have beneficial effects both in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In this sense, Malvindi et al, [16] combined fluorescence quantum rods with an ester bond with succinyl DA which can be hydrolyzed by cellular enzymes to release the prodrug inside the cells. This DDS was covered with a galactose shell which can be recognized by the GLUT-1 transporters to mediate its diffusion across the BBB.…”
Section: Dss For Dopamine Deliverymentioning
confidence: 99%
“…In this sense, Malvindi et al, [16] combined fluorescence quantum rods with an ester bond with succinyl DA which can be hydrolyzed by cellular enzymes to release the prodrug inside the cells. This DDS was covered with a galactose shell which can be recognized by the GLUT-1 transporters to mediate its diffusion across the BBB.…”
Section: Dss For Dopamine Deliverymentioning
confidence: 99%
“…This phenomenon is referred to the EPR effect, especially occurred in most solid tumors [80][81][82][83][84][85][86][87]. Because of their nano scale size, the nanocarrier based drug delivery system can pass through blood-brain barrier [88,89]. Investigators found that those carriers can either open up a tight junction or undergo endocytosis to cross the blood-brain barrier, which prevents the passage of most traditional drugs [90][91][92][93][94][95].…”
Section: Targeting Lscs By Nanomedicinementioning
confidence: 99%
“…94 Other formulations designed to treat neurodegenerative disorders include chitosan nanoparticles loaded with subfragments of amyloid-beta, which permeated the blood-brain barrier and were nonimmunogenic; 95 a transdermal nanoemulsion gel containing ropinirole to treat Parkinson's disease, which improved the relative bioavailability of the drug with no toxicity; 96 and dopamine incorporated into a smart nanocrystal conjugated with PEG and covered by a carbohydrate shell allowing recognition of glucose transporter 1. 97 Detailed reviews on current nanotechnology-based delivery systems applied to the treatment of Alzheimer's disease and Parkinson's disease have been recently published.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%